(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The adoption of banking alternative delivery channels has been very slow. Since adoption of banking self-service technologies by customer means cost cutting and profits for the bank, it becomes imperative to look into the demographic profile of the customer. This helps banks in devising strategies to direct customers to other channels. An overview of respondents’ socio-economic characteristics as the socio-economic characteristics may have direct or indirect bearing on their perceptions shaping his intentions to use the technology. The objective of this study was to study the distribution of banking customers in public and private banks based on their demographic profile in Chandigarh region. A sample of 300 respondents each was drawn using branch intercept technique from each of these banks. The study concluded that the clientele of young customers is more in private sector banks. Younger people with higher level of education and income were associated with the private sector banks as compared to the public sector banks.